Body mass index and leukocyte telomere length in adults: a systematic review and meta‐analysis. Issue 3 (25th October 2013) - Müezzinler, A.; Zaineddin, A. K.; Brenner, H.
Summary The objective of this study was to provide a systematic review and meta‐analysis of studies on the relationship between body mass index (BMI) and leukocyte telomere length (LTL). Relevant studies were identified by a systematic search of MEDLINE, Embase and Web of Knowledge databases. Pooled correlation and regression coefficients were calculated using meta‐analysis methods for both cross‐sectional and longitudinal studies. Studies without suitable data for meta‐analysis were summarized separately. Overall, 29 studies were included, of which 16 were eligible for meta‐analysis, including two longitudinal studies. The majority of studies reported an inverse relationship between BMI and telomere length. For cross‐sectional studies, the pooled estimates for correlation and regression coefficients were −0.057 (95% confidence interval [CI]: −0.102 to −0.012) and −0.008 kBP kg m−2 (95% CI: −0.016 to 0.000), respectively. The two longitudinal studies were small (70 and 311 subjects), covered different age ranges and yielded inconsistent results. No evidence of any gender difference was observed. Despite some variation between studies and very limited data from longitudinal studies, the results of this meta‐analysis suggest a biologically plausible inverse association between BMI and LTL in adults. However, the associations require clarification, in particular by large longitudinal studies with careful control for possible confounding factors in overall, age‐ and sex‐specific analyses.